THE TEACHERS’ ABILITY TO DEVELOP THE STEM-BASED SCIENCE LEARNING PLAN - Toto Toto (Universitas Galuh, 2022)
This study aims to determine the teachers’ ability in developing STEM-based science learning plan. This study departs from the science teachers’ problem that are required to prepare a science learning plan using STEM approach. It is the linking approach between Science, Technology, Engineering and Mathematics which is categorized as new approach for teachers. This study involved 29 science teachers in Ciamis regency who joined STEM-based science learning workshop held by Biology Education department of Galuh University. The study employed documentation studies which was carried out by analysing the STEM-based science learning plan prepared by workshop participants. The findings showed that the teachers’ ability in developing STEM-based science learning plans was moderate.Keywords: Science Learning Plan, STEM Approach